Solubility Enhancement of Lawsone by Complexation with Beta Cyclodextrin - Francis, Shincy Mariya; Xavier, Elizabeth N (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: Lawsone is a phyto-constituent obtained from the leaves of the Lawsonia inermis. It has antibacterial, antifungal, antiviral, wound healing, antiparasitic, tuberculostatic, anti-fertility, analgesic, anti-inflammatory, enzyme inhibitory, nematicidal, anticoagulant, and protein glycation inhibitory activities. It has poor water solubility (hydrophobic), poor bioavailability, and poor dissolution characteristics. Aim: The purpose of this research is to improve the aqueous solubility of Lawsone by preparing the inclusion complexes of Lawsone with beta-cyclodextrin. Materials and Methods: Inclusion complexes of Lawsone were prepared by different methods such as physical mixture, kneading method and co-precipitation method. Characterization of the complexes were done by Fourier Transform Infrared (FTIR) spectroscopy and in vitro dissolution study. Differential scanning calorimetry (DSC), Nuclear Magnetic Resonance spectroscopy (NMR), and Powder X-Ray Diffraction (PXRD). were used to evaluate the co-precipitation technique inclusion complexes. Antimicrobial studies of complexes against Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Bacillus subtilis (B. subtilis), and Pseudomonas aeruginosa (P. aeruginosa ) were done by colony counting method. Results: Phase solubility study revealed the molar ratio of Lawsone to betacyclodextrin in the complex is 1:1. At the third hour, the drug release was 64%, 78%, 93%, and 97% for pure drug, physical mixture, inclusion complexes formed by kneading technique and co-precipitation technique respectively. DSC, NMR, and PXRD confirmed the formation of complexes of Lawsone. The order of antibacterial activity of inclusion complexes was E. coli > B. subtilis > P. aeruginosa > S. aureus.
Keywords: Lawsone; Beta-cyclodextrin; Inclusion complexes; Kneading method; Co-precipitation method